The relationship between social support, resilience and career adaptation among trainee counsellors in Malaysia: a conceptual study - Wan Othman, Wan Norhayati; Ismail, Asmah; Engku Kamarudin, Engku Mardiah; Ramlee, Noorlimunierah (Human Resource Management Academic Research Society, 2024)
Career adjustment describes the level of readiness of an individual which includes attitude, competence and behavior in adapting to the chosen career environment. In the process of making career adjustments, social support whether from family, friends or significant individuals can contribute to personal well-being. However, resilience is also a contributing factor to the success of a trainee counselor to survive when faced with any threatening and risky situation that can ultimately affect commitment and performance if not overcome. This research is a conceptual study that examines the relationship between social support and resilience with career adjustment among trainee counselors in Malaysia. The findings of this study can be used by parties involved in designing appropriate programs to improve the professionalism of trainee counselors in Malaysia.